2018
DOI: 10.1155/2018/6141845
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Salivary Profiles as Novel Biomarkers for Oral Diseases

Abstract: The Global Burden of Oral Diseases affects 3.5 billion people worldwide, representing the number of people affected by the burden of untreated dental caries, severe periodontal disease, and edentulism. Thus, much more efforts in terms of diagnostics and treatments must be provided in the fight of these outcomes. In this sense, recently, the study of saliva as biological matrix has been identified as a new landmark initiative in the search of novel and useful biomarkers to prevent and diagnose these conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 157 publications
0
52
0
Order By: Relevance
“…Some studies reported that plaque bacteria are released into saliva [9,33], and saliva provides a niche for both anaerobic and aerobic bacteria [34]. Furthermore, saliva is a biomarker that reflects oral health and systemic condition [35,36]. Thus, saliva evaluation has several advantages, especially in large-scale epidemiological studies or caries screening.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that plaque bacteria are released into saliva [9,33], and saliva provides a niche for both anaerobic and aerobic bacteria [34]. Furthermore, saliva is a biomarker that reflects oral health and systemic condition [35,36]. Thus, saliva evaluation has several advantages, especially in large-scale epidemiological studies or caries screening.…”
Section: Discussionmentioning
confidence: 99%
“…When saliva is compared to other bio-fluids, it becomes very attractive due to the non-invasive nature of sampling, low cost and greater clinical safety, which contributed to the idea that it represents “a window of opportunity” for modern medicine. A good example for this concept is the determination of salivary cortisol, enhanced by similar levels with serum cortisol and easy conservation (1–2 days at room temperature or 1 week at +4 °C) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is a complex biological fluid secreted in the mouth by three main pairs of salivary glands, namely the parotid, the submandibular, and the sublingual, which generate 0.75–1.5 L daily. The compositions of their secretions depend on the sympathetic and parasympathetic stimulation, circadian rhythm, health status, eating habits and drug intake [ 138 , 139 ]. Considering the direct relation between the salivary gland and the nervous system, as the facial nerve innervates the sublingual and submandibular glands through the submandibular ganglion and the glossopharyngeal nerve innervates the parotid gland through the otic ganglion, saliva could represent an important source of biomarkers for nervous system disorders [ 139 , 140 ].…”
Section: Saliva Biomarkersmentioning
confidence: 99%